Towards high light conversion efficiency from photo-fermentative hydrogen production of Arundo donax L. By light–dark duration alternation strategy. (January 2022) - Jiang, Danping; Zhang, Xueting; Jing, Yanyan; Zhang, Tian; Shui, Xuenan; Yang, Jiabin; Lu, Chaoyang; Chen, Zhou; Lei, Tingzhou; Zhang, Quanguo
Highlights: 24 h dark + 24 h light duration alternation improved the HY by 6.7 %. LCE was enhanced by 114.7 % via 24 h dark + 24 h light duration alternation. Light period after inoculation had the closest relation with average HPR. Decreased dark period after inoculation would increase the HY. Abstract: Suitable illumination project would help in achieving high light conversion efficiency (LCE) for photo-fermentation. This study proposed an improvement strategy for LCE of photo-fermentative hydrogen production (PFHP) with a photosynthetic consortium by adopting light–dark duration alternation. For this purpose, 6 projects (continues light, 24 h light + 24 h dark, 24 h dark + 24 h light, 48 h light + 48 h light, 48 h dark + 48 h light, and continues dark) light disturbances were carried out to estimate the strategy. The fluctuation of cell growth (OD660) was corresponded to the light–dark alternation. 24 h dark + 24 h light alternation achieved the maximum hydrogen yield (HY) of 390.9 mL/g TS cell (6.7 % higher than continuous light) and maximum improvement of LCE of 114.7%. Moreover, heat map analysis revealed that the light period after inoculation had the closest relation (Pearson's r = 1) with the average hydrogen production rate (HPR) of photo-fermentation. Besides, decreased dark period after inoculation would increase the hydrogen yield of photo-fermentation.